Historical land-cover/use in different slope and riparian buffer zones in watersheds of the State of São Paulo, Brazil - Da Silva, Alexandre Marco [UNESP]; Nalon, Marco Aurélio; Kronka, Francisco José Do Nascimento; Alvares, Clayton Alcarde; De Camargo, Plinio Barbosa; Martinelli, Luiz Antonio (My University, 2007)
Information about the land cover of a region it is a key information for several purposes. This paper aimed to elaborate land-cover maps using digital satellite images obtained in 1997 from seven watersheds (Piracicaba, Moji-Guaçu, Alto Paranapanema, Turvo Aguapeí, Peixe, and São José dos Dourados) located in the State of São Paulo, southeastern Brazil. Additionaly, this study evaluated the relationship between land-cover and slopes of the terrain of the seven watersheds. A third objective was to estimate the percentage of riparian vegetation currently remaining along the streams in a 30-meter width buffer zone. Three research questions were posed: i) What is the dominant land-cover of these watersheds? ii) Is the riparian vegetation well preserved in the 30m width buffer zone? If not, iii) what is the dominant land-cover in these areas and what would be the cost of recovering such areas? Pasture was the predominant land-cover, occurring in approximately 50% of the entire study area, while sugar cane (Saccharum officinarum) (14%) constituted the second most frequent land-cover. Approximately 50% of the area of the seven basins is considered flat (40%) or smoothly rolling (10%). The terrain only becomes hillier in the Piracicaba and Alto Paranapanema basins, where a little less than 50% have slopes higher than 8%. The total riparian buffer strip zone occupied an area equivalent to approximately 6,200 km 2. From this total, only 25% is preserved. Pasture is the main land-cover of the riparian buffer strip zone.
Keywords: Catchments; Geoprocessing; Land management; Land planning; Rivers